Estimation of coupling coefficient and refractive index for fused coupled fibers - Saktioto, Toto; Ali, Jalil; Fadhali, Mohammed; Zainal, Jasman (2008)
Fiber couplers are widely used in telecommunication and industry as a passive splitting power device. The effective power coupling and transmitting from one fiber to another is mainly determined by both coupling length and coupling coefficient. Coupling length can be calculated directly but for coupling coefficient it depends upon the refractive index and separation fiber axis. After fusion processes of two SMF-28eÂ® couplers, the refractive index is unknown due to change in the radius of fiber (rcladd<40ïm and rcore<1.5ïm). Coupling coefficient range is obtained from a distribution of coupling ratio and compared with the empirical formula which also enables to calculate refractive index. In this experiment, coupling coefficient in the range of 0.6-0.9/mm is calculated as a function of separation fiber axis and refractive index of core and cladding. The result shows a good correlation between experimental results and theoretical calculation.